Badanie wpływu zaburzeń na obciążenia estymatora parametru położenia oraz parametru skali w populacji - Zmyślona, Beata (The outliers influence on estimate bias of location and scale parameters in population research, 2008)
Outliers have an influence on the estimator bias and estimator variance. We have two tools to study this influence, namely the influence function and the change-of-variance function. The influence function has three characteristics: the gross-error sensitivity, the rejection point and the local-shift sensitivity. In this paper we present some examples of influence function calculation and its characteristics for some estimates: the arithmetic mean, the sample variance and the median.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 56-70